Conceptualization of Supplier Involvement in Product Development Based on a Systematic Review of 47 Definitions - Filip Flankegård; Glenn Johansson; Anna Granlund; Peter E. Johansson (Logistics, 2024)
Background: Supplier involvement in product development has proven beneficial for companies and is a phenomenon researched in various domains. The definitions of supplier involvement represent points of origin and dimensions addressed in research. Still, there is no overview of these definitions and dimensions. This study reviews current definitions of the phenomenon of supplier involvement in product development and develops a conceptual model outlining its main dimensions. Methods: A systematic literature review is conducted to provide an overview of explicit definitions of supplier involvement in product development. By identifying the elements of these definitions, a conceptual model is developed to demonstrate how the phenomenon has been conceptualized in literature. Results: The results include an overview of 47 explicit definitions of supplier involvement in product development, a conceptual model including the identified dimensions, research gaps, and questions for future research. Conclusions: Supplier involvement in product development is a complex phenomenon with interdependencies between its key dimensions. A conceptual model of supplier involvement is presented, which is useful for categorizing research to identify research gaps and avenues for future research.